Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2174/157339511796196584
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Regulatory T Cells to Antigen Expressed in the Retina

Abstract: Regulatory T cells (Tregs) are generated to antigens (Ag) found in the retina. Some Tregs are the result of ectopic expression of the retinal Ags in the thymus, where developing T cells are committed to enter the regulatory lineage. However, the generation of retinal Ag-specific Tregs independent of the thymus was uncertain. Our studies show that Tregs can be generated from mature, peripheral T cells based on exposure to retinal Ags. These peripherally induced Tregs limited immune responses and experimental au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…However, the double Tg mice had a reduced delayed-type hypersensitivity (DTH) response to βgal compared to βgalTCR mice. In total, our results suggested that the down regulation of immune responses associated with retinal βgal was due the generation of Ag-specific CD4 + CD25 + Tregs from naïve CD4 + precursors and was dependent on the presence of retinal βgal (3437). To promote analysis of the nature of retinal Ag-specific Tregs the model was moved onto the B6 background.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…However, the double Tg mice had a reduced delayed-type hypersensitivity (DTH) response to βgal compared to βgalTCR mice. In total, our results suggested that the down regulation of immune responses associated with retinal βgal was due the generation of Ag-specific CD4 + CD25 + Tregs from naïve CD4 + precursors and was dependent on the presence of retinal βgal (3437). To promote analysis of the nature of retinal Ag-specific Tregs the model was moved onto the B6 background.…”
Section: Resultsmentioning
confidence: 76%
“…However, recent studies have shown that iTregs induced to tissue-specific self-Ag can regulate Teffs (32, 33). Similarly, we have used Tg mice expressing E. coli beta-galactosidase (βgal, arrβgal mice) in retina photoreceptor cells in conjunction with T cell receptor (TCR)-Tg mice specific for βgal to demonstrate that a consistent outcome of retinal βgal expression is a down regulation of systemic immune responses to βgal that is, in part, due to the induction of Tregs from naïve, peripheral βgal-specific CD4 + cells (3437). …”
Section: Introductionmentioning
confidence: 99%
“…This finding is in agreement with previous reports that described expression of recoverin and a small number of other retinal antigens in mouse and human thymus, where the formation of natural regulatory T cells (nTreg) is known to occur in response to self-antigen exposure ( 23 , 24 ). In addition, inducible regulatory T cells (iTreg) may also be generated and supported by expression of recoverin and other retinal antigens by the retina itself ( 25 , 26 ). Recoverin-specific nTreg or iTreg cells in the retina would be expected to provide local protection from immune attack by secreting IL-10, and possibly expression of other immune regulatory factors in response to presentation of recoverin peptides by local antigen presenting cells ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Retina-specific Treg cells are produced in response to antigens found in the retina. These can either be natural Tregs, which are generated against retinal antigens expressed in the thymus, or these can be generated independently of thymus from mature peripheral T cells based on exposure to antigens ( 103 ). In the retina, this cell population has been associated with uveoretinitis, where an increased number of CD4 + CD25 + Tregs was detected in spleen and eye ( 104 ).…”
Section: Protector or Promoter: Regulatory T Cellsmentioning
confidence: 99%